1998
DOI: 10.1615/critrevoncog.v9.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Involvement in Cancer Anorexia/ Cachexia: Role of Megestrol Acetate and Medroxyprogesterone Acetate on Cytokine Downregulation and Improvement of Clinical Symptoms

Abstract: The characteristic clinical picture of anorexia, tissue wasting, loss of body weight accompanied by a decrease in muscle mass and adipose tissue, and poor performance status that often precedes death has been named the cancer-related anorexia/cachexia syndrome (CACS). Chronic administration of pro-inflammatory cytokines, including interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor (TNF) either alone or in combination, is capable of reproducing the different features of CACS. High serum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 0 publications
1
69
0
5
Order By: Relevance
“…However, this gain had been mainly attributed to an increased fat mass, not to muscle mass and had no evidences of benefit in terms of quality of life or survival 23, 24. The mechanisms of MA responsible for contributing to increased body weight in cachectic patients are not completely clear, but some studies showed that, in addition to stimulating appetite, it also had an effect on both metabolic and inflammatory mechanisms 25, 26. Concerning skeletal muscle, previous studies performed in our laboratory in experimental animals showed a clear anabolic effect of MA in skeletal muscle.…”
Section: Introductionmentioning
confidence: 95%
“…However, this gain had been mainly attributed to an increased fat mass, not to muscle mass and had no evidences of benefit in terms of quality of life or survival 23, 24. The mechanisms of MA responsible for contributing to increased body weight in cachectic patients are not completely clear, but some studies showed that, in addition to stimulating appetite, it also had an effect on both metabolic and inflammatory mechanisms 25, 26. Concerning skeletal muscle, previous studies performed in our laboratory in experimental animals showed a clear anabolic effect of MA in skeletal muscle.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies suggest that the mechanisms by which MEGACE stimulates appetite and weight gain is related to decreased production and release of pro-inlammatory cytokines (IL-1, IL-6, and TNF-α) as well as the stimulation of NPY in the hypothalamus [111][112][113]. Another progestogen, medroxyprogesterone acetate, was demonstrated through in vitro experiments to decrease the production of cytokines and serotonin by PBMC of cancer patients [112,113].…”
Section: Progestogensmentioning
confidence: 99%
“…Another progestogen, medroxyprogesterone acetate, was demonstrated through in vitro experiments to decrease the production of cytokines and serotonin by PBMC of cancer patients [112,113].…”
Section: Progestogensmentioning
confidence: 99%
See 1 more Smart Citation
“…[129][130][131][132][133] As an appetite stimulant in HD patients, megestrol acetate was found to improve appetite, increase energy and protein intake and increase dry weight and to improve quality of life. [134][135][136] The downside is that it can induce many side effects such as headaches, dizziness, confusion, diarrhea, hyperglycemia, thromboembolic phenomena, breakthrough uterine bleeding, peripheral edema, hypertension, adrenal suppression, and adrenal insufficiency.…”
Section: 87mentioning
confidence: 99%